Characteristics of Scorpionism in Montenegro - Andric, Bogdanka; Idrizovic, Ramiza; Jovanovic, Milan (International Journal of Psychosocial Rehabilitation, 2020)
Scorpionism is a significant health problem in many parts of the world due to the toxic stings, which can endanger the health and lives of the people. The severity of clinical manifestations and the problem is not the efficiency of therapeutic treatment; it presents an additional problem. Montenegro is an endemic area for two types of scorpions: Mesobuthus gibbosus and Euscorpius italicus. The severity of poisoning depends on many factors, such as previous health condition, age of the victim, the location of the bite, penetration depth, scorpion’ species, and the degree of his agitation. After scorpion bites, become noticeable local and general symptoms. Especially dangerous are the symptoms we're presenting of the heart, affecting the CNS, those that lead to the serious changes in the respiratory system, and cause Hepatic Uremic Syndrome (HUS). The treatment of scorpion bites and poisoning is complex and controversial, in particular regarding the utility of the antivenins and symptomatic treatments that must be associated. Antidotes for poison from different scorpion species are very specific. Their efficiency is closely related to the geographical region and the scorpion species from which it is obtained. In the period of 2009-2015, 15 cases of scorpionism were officially registered in Montenegro, but it can be assumed that the real number is much higher. In 12 cases, it was a Mesobuthus gibbosus, the most common type of scorpion in Europe. In 3 cases it was a scorpion sting, Euscorpius italicus, living in all parts of Montenegro and the Montenegrin coast. In our series, fatal cases were not registered. In two cases, neurological damages are registered. In 2 cases, which were manifested by involuntary muscle twitches in extremities where he sustained stab wounds, chronic degenerative changes were found at EMG investigation. In another case, a year after scorpion bites, he developed transient hemiparesis, which lasted more than one year.